Enhancing Arabic Listening and Vocabulary Acquisition through AI-Powered Music: A Study on Suno AI - Solehudin, Muhamad; Hanifansyah, Nur; Izzuddin, Iqbal Fathi (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
This study explores the impact of AI-generated music, specifically through the Suno AI platform, on enhancing Arabic listening skills (maharah istima') and vocabulary acquisition at Darullughah Wadda’wah Boarding School (Pesantren). A qualitative approach was employed over a 3-week period, involving 120 students aged 16 to 18. The findings reveal that AI-powered music significantly improved student motivation, engagement, and learning outcomes. Students demonstrated better vocabulary retention and listening comprehension, facilitated by the contextual use of lyrics in AI-generated songs. However, the short duration of the study posed challenges for mastering all introduced vocabulary. This research suggests that integrating AI-generated music into Arabic language education offers a promising, engaging alternative to traditional methods, particularly in enhancing receptive language skills. Future studies could extend the duration and explore the impact on other language skills such as speaking and writing.